2003
DOI: 10.1364/josaa.20.001094
|View full text |Cite
|
Sign up to set email alerts
|

Mode analysis of spreading of partially coherent beams propagating through atmospheric turbulence

Abstract: The spreading of partially coherent beams propagating through atmospheric turbulence is studied by use of the coherent-mode representation of the beams. Specifically, we consider partially coherent Gaussian Schell-model beams entering the atmosphere, and we examine the spreading of each coherent mode, represented by a Hermite-Gaussian function, on propagation. We find that in atmospheric turbulence the relative spreading of higher-order modes is smaller than that of lower-order modes, whereas the relative spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(91 citation statements)
references
References 10 publications
0
90
0
1
Order By: Relevance
“…Gbur and Wolf (2002) looked theoretically at the spreading of partially coherent beams in random media, and noted that they are "resistant" to turbulence; this was demonstrated experimentally by Dogariu and Amarande (2003). Similar theoretical results were found by Ponomarenko, Greffet, and Wolf (2002) using a Hilbert-space method, and by Shirai et al (2003) using the coherent mode representation. Long-distance propagation of partially coherent beams was studied soon after by Salem, Shirai, Dogariu, and Wolf (2003).…”
Section: Direct Applications Of Coherence Theorymentioning
confidence: 60%
See 1 more Smart Citation
“…Gbur and Wolf (2002) looked theoretically at the spreading of partially coherent beams in random media, and noted that they are "resistant" to turbulence; this was demonstrated experimentally by Dogariu and Amarande (2003). Similar theoretical results were found by Ponomarenko, Greffet, and Wolf (2002) using a Hilbert-space method, and by Shirai et al (2003) using the coherent mode representation. Long-distance propagation of partially coherent beams was studied soon after by Salem, Shirai, Dogariu, and Wolf (2003).…”
Section: Direct Applications Of Coherence Theorymentioning
confidence: 60%
“…A modal representation can also be applied to the propagation of fields through random media, as was demonstrated theoretically by Shirai, Dogariu, and Wolf (2003) in a study of the spreading of beams in turbulence. Schwartz and Dogariu (2006) have suggested that a modecoupling approach could be used to study more general properties of a turbulence-degraded beam.…”
Section: The Coherent Mode Representationmentioning
confidence: 99%
“…Many theoretical and experimental investigations on the behavior of a propagating beam show Sphumelele C. Ndlovu: School of Chemistry and Physics, University of KwaZulu-Natal, Scottsville, Pietermaritzburg 3209, RSA *Corresponding Author: Naven Chetty: School of Chemistry and Physics, University of KwaZulu-Natal, Scottsville, Pietermaritzburg 3209, RSA, E-mail: ChettyN3@ukzn.ac.za that atmospheric turbulence leads to intensity perturbations [3][4][5][6][7][8][9]. These perturbations result from refractive index uctuations due to thermal uctuations in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…A historical example illustrating the relevance of light statistics is found in astronomy where the star size was estimated from the measurement of the degree of coherence (DoC) [4]. Modern coherence-based techniques include ghost imaging [5,6], coherence controlled microscopy [7,8], lithography [9,10], and characterization of atmospheric [11] and plasma [12] instabilities. Moreover, the use of partially coherent light increases the transmission capacity of free-space communications [13] and improves information encoding [14].…”
Section: Introductionmentioning
confidence: 99%